Keeping It Real: The Impact of HRD Internships on the Development of HRD Professionals. (May 2017) - Sawyer, Katina
The Problem: Participation in internships may provide undergraduate human resource development (HRD) students with practical experience necessary to be successful in the field. However, research is lacking which examines the impact of HRD internship experiences on professional development and career trajectories. Research is also limited which provides guidance on how to distinguish which undergraduate internships may be most valuable. The features which make internships most effective in preparing students for their chosen careers warrant further examination, specifically within HRD. Relatedly, it is important to understand which internship experiences are most likely to develop HRD competencies for undergraduate students. The Solution: Qualitative and quantitative data were collected from HRD professionals who had participated in an HRD internship while they were undergraduate students. These data were analyzed, using qualitative and quantitative methods, to better understand the structure and focus of student HRD internships. Specifically, while the data are preliminary, this study generated insights regarding the extent to which effective internships were able to promote the development of key HRD skillsets, and which skillsets were most likely to be enhanced. The Stakeholders: Using the results of this analysis, educational institutions can better understand how to locate effective internships for students. In addition, students can utilize these data to better recognize valuable internship experiences in the future.